Photonics. (2020) - Dobrzynski, Léonard; Akjouj, Abdellatif; Boudouti, El Houssaine El; Leveque, Gaetan; Al-Wahsh, Housni; Pennec, Yan; Ghouila-Houri, Cecile; Talbi, Abdelkrim; Djafari-Rouhani, Bahram; Jin, Yabin
No abstract available